Pengembangan Lembar Kegiatan Peserta Didik Berbasis Saintifik Pada Mata Pelajaran Administrasi Umum Kelas X OTKP Di SMKN 1 Lamongan - Roya Praspita; Brillian Rosy (Universitas Negeri Surabaya, 2020)
This study aims to produce a prototype of teaching materials in the form of Scientific Student based Activity Sheet on General Administration Subjects in Class X OTKP Odd Semester involving experts and students to obtain LKPD eligibility as well as student responses regarding LKPD developed. This type of research is a type of research development using the 4D model that is define, design, develop, disseminate but the research conducted by researchers did not reach the disseminate stage because the purpose of this study was to obtain a product prototype and the results of eligibility from experts. The subjects of the study were 20 students of class X OTKP 1ND Lamongan, using questionnaire responses of students while for experts using validation sheets. The results of this study indicate that the Student Activity Sheet which was developed in the subjects of General Administration class X OTKP using 4D models namely define, design, develop, disseminate, however, researchers only reached the develop stage because the purpose of this study was to obtain a product prototype and product viability results. In terms of material, language, and graphic aspects, the total percentage of 88.06% was included in the very feasible category. Each percentage of material experts 84.2% with very decent interpretation criteria, 91% of linguists with very decent interpretation criteria, 89% graphic experts with very decent interpretation criteria. The response results of students get 96.3% with very good criteria. Thus the development of Scientific-based LKPD in General Administration Subjects Class X OTKP obtained results worthy of use in teaching and learning activities in General Administration.